DAMPAK PANDEMI COVID-19 TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI WILAYAH SOLO RAYA - Arrum Puspita Sari; Durotun Nafisah; Fitri Susanti; Hesti Eka Setianingsih; Nur Mila Hayati (Academica: Journal of Multidisciplinary Studies, 2021)
This study aims to determine the impact of the Covid-19 pandemic on motor vehicle taxpayer compliance in the Solo Raya area. This type of research is qualitative research. Data collection techniques through interviews using primary data and data analysis techniques by means of structrured respondent interviews. Respondents in this study were motorized vehicle taxpayers in the Solo Raya area. The conclusion from the results of this study shows that the Covid-19 pandemic has an impact on the weakening of the community's economy which causes a decrease in the level of taxpayer compliance in paying motor vehicle taxes and there are people who do not pay motorized vehicle tax. However, most taxpayers still pay motor vehicle taxes on time.Keywords: Taxes; Impact of the Covid-19 Pandemic; Taxpayer Compliance; Motor Vehicle Taxes.